Intensity-modulated radiotherapy (IMRT) versus three-dimensional conformal radiotherapy (3DCRT) as treatment plans for head and neck tumours - Abd Al-Taj Abd Ali Khaleel; Siham Sabah Abdullah; Sabbar Shukri Al-Bayaty; Nabaa Mohammad Ali Alazawy; Abdulrahman Mohammed Abdulbaqi (Journal of the Pakistan Medical Association, 2024)
Objectives: To compare intensity-modulated radiation therapy with three-dimensional conformal radiation therapy 3DCRTwith respect to dose coverage for target volume. Method: The cross-sectional study was conducted at Al-Amal National Hospital, Baghdad, Iraq, from November 2020 to March 2021 and comprised patients with head and neck cancerous tumours. The patients underwent computed tomography scans, and were subsequently subjected to three-dimensional conformal radiotherapy and intensity-modulated radiotherapy treatment planning techniques on the basis of Monaco 5.1. The oncologist selected the better plan depending on evaluation parameters for each patient who was then irradiated with X-ray treatment. Data was analysed using SPSS 24. Results: There were 30 patients, 17 (57%) females and 13 (43%) males with the age range of 19-45 years. Of the total, 28 received chemotherapy and 6 patients underwent brain surgery. The intensity-modulated radiation therapy resulted in significant coverage of the tumour than the three-dimensional conformal radiation therapy in phase 1 (p<0.00001) and phase II (p=0.0023). The intensity-modulated radiation therapy technique achieved a lower homogeneity value (p=0.0004) and higher conformity value (p<0.00001) than three-dimensional conformal radiation therapy. In phase II, no significant homogeneity index was found between the two therapies (p=0.072). The intensity-modulated radiation therapy showed significantly better conformity compared to three-dimensional conformal radiation therapy (p<0.00001). Conclusion: The intensity-modulated radiation therapy significantly improved coverage, plan conformity, and humongous dose distribution for head and neck tumours compared to the three-dimensional conformal radiation therapy 3DCRT. Key Words: Radiotherapy, Monaco, X-Rays, Radiotherapy, Conformal, Head and Neck, Tomography, Brain